2022
DOI: 10.3390/nano12010174
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of Water Properties inside Carbon Nanotubes

Abstract: Confined water inside carbon nanotubes (CNTs) has attracted a lot of attention in recent years, amassing as a result a very large number of dedicated studies, both theoretical and experimental. This exceptional scientific interest can be understood in terms of the exotic properties of nanoconfined water, as well as the vast array of possible applications of CNTs in a wide range of fields stretching from geology to medicine and biology. This review presents an overreaching narrative of the properties of water i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 211 publications
(509 reference statements)
0
34
0
Order By: Relevance
“…Comparison with other systems exhibiting sub-diffusion. It is interesting to note some striking similarities of this system with water inside hydrophobic carbon nanotubes (CNTs) 49 . In narrow CNTs (d < 1.0 nm) water is found to diffuse as a single file by a very large number of studies, both theoretical [27][28][29] and experimental 17,18 .…”
Section: Resultsmentioning
confidence: 94%
“…Comparison with other systems exhibiting sub-diffusion. It is interesting to note some striking similarities of this system with water inside hydrophobic carbon nanotubes (CNTs) 49 . In narrow CNTs (d < 1.0 nm) water is found to diffuse as a single file by a very large number of studies, both theoretical [27][28][29] and experimental 17,18 .…”
Section: Resultsmentioning
confidence: 94%
“…For instance, it was recently discovered that diffusion-osmotic transport is crucial to the ion diffusion process across nanofluidic channels, relevant in the osmotic energy conversion. This requires detailed understanding about the transport properties of water across nanotubes. Both experimental and simulation studies have suggested that the diffusion of water inside a cylindrical nanotube can be significantly different from the bulk. Diffusivity of water through a narrow carbon nanotube (CNT) was reported to be lower than bulk .…”
Section: Introductionmentioning
confidence: 99%
“…Research on the diffusion of water molecules in artificial water channels is of interest to many researchers because it can lead to new designs of synthetic channels with similar performance to biological water channels. In recent years, water in carbon nanotubes (CNTs) has been studied extensively using different experimental techniques [ 12 , 13 ] and molecular dynamics simulations [ 14 ]. These methods extracted valuable information, such as the temperature dependence of water diffusion in nanohydrophobic confinements, which is of great interest in many applications.…”
Section: Introductionmentioning
confidence: 99%